A Review of SUCCESS! in Clinical Laboratory Science<source>SUCCESS! in Clinical Laboratory Science</source>; <person-group person-group-type="author"> <name name-style="western"> <surname>Ciulla</surname> <given-names>Anna</given-names> </name> <name name-style="western"> <surname>Lehman</surname> <given-names>Donald</given-names> </name> </person-group>; ( <year>2010</year>). <publisher-name>Prentice Hall</publisher-name>, <publisher-loc>Upper Saddle River, NJ</publisher-loc>. <fpage>1176</fpage> pages. - Rebecca Buxton* (American Society for Microbiology, 2011)
Review of: SUCCESS! in Clinical Laboratory Science; Anna Ciulla and Donald Lehman; (2010). Prentice Hall, Upper Saddle River, NJ. 1176 pages